Analysis of Combined Treatment with Azathioprine and Thiotriazoline on the Course of Chronic Liver Disease in Male Rats - Oleh, Shmanko (Asian Journal of Pharmaceutics (AJP), 2018)
Aim and Scope: Hepatotoxicity of medications is an urgent problem all over the world. Such drugs are particularly dangerous during chronic liver disease. Therefore, today relevant research is devoted to the problem of hepatotoxicity of drugs, and to finding means for its prevention. The purpose of the study was to analyze the combined effect of azathioprine and thiotriazoline on the course of chronic liver disease with the presence of hepatocellular insufficiency in male rats. Materials and Methods: For the study, 30 sexually mature white male rats weighing 180–220 g were used, of which the control group consisted of 6 sexually mature white male rats. To model hepatocellular insufficiency, partial hepatectomy was performed. Experimental animals were divided into three groups: Groups 1–8 animals, comparison group without treatment, Groups 2–8 animals that received azathioprine for 20 days, and Groups 3–8 animals that received azathioprine and thiotriazoline for 20 days; then their blood sample was taken for investigation. Results and Discussion: Comparing the results of azathioprine with those of azathioprine combined with thiotriazoline, significant advantages of combined treatment were found: Normalization of levels of total bilirubin, total blood protein, cholesterol, a more significant decrease in alanine aminotransferase, and the absence of bone marrow suppression phenomena. Conclusion: Combined use of thiotriazoline and azathioprine in hepatocellular insufficiency prevents the development of toxic effects of azathioprine and may be recommended for use in patients with the chronic liver disease. Future studies on the use of thiotriazoline as a concurrent therapy to protect the liver during treatment with hepatotoxic drugs are recommended.